BEING AN OUTLAW. KAFKA’S PHILOSOPHY OF LAW - Prole , Dragan (Glasnik Advokatske komore Vojvodine, 2020)
In many places in Kafka's literature, the idea has been varied that no matter how bad things are in the human world, man's tendency to protect himself by creating illusory notions about him is even worse. If the origin of the most notorious among fatal illusions is related to the need for security, refuge, protection, to the same need that established the necessity of passing laws and developing the legal system, then significant pages of Kafka's literature can be read on the horizon of a kind of negative anthropology. Its premises seem to testify to the betrayed human aspiration to protect every individual through the courts and rights. The author pays special attention to the question of what it means to be outside the law, emphasizing that a man from the village who remains before the law metaphorically represents the Jewish refugees from Galicia who remained in front of the gates of Prague in 1914.
Keywords: Kafka, philosophy of law, security, being-out-of-law